SPEAKING ABILITY IMPROVEMENT THROUGH CERING IMAGE MEDIA IN GROUP A TK PKK AKE TALAGA IN TIDORE ISLANDS - Rita Samad (PEDAGOGIK, 2020)
Speaking is the ability to pronounce articulated sounds or words to express, express, and convey thoughts, ideas, and feelings in Tarigan (1985: 98) results from initial observations with a total of 10 children aged 4 to 5 years, it seems that they are still underdeveloped in speaking this is due to the lack of teachers in implementing learning media, especially serial image media. So the researchers tried to solve it by using serial image media to improve children's ability to speak. With the formulation of the problem, how do you improve the ability to speak through serial media for group A TK PKK Ake Talaga in Tidore Islands?, The research objective was to describe the children speaking through serial pictures. The research is classroom action research (CAR), using qualitative descriptive data analysis techniques and percentages. Data collection techniques used observation and documentation techniques, in the evaluation in cycle I, namely, in speaking well according to the serial image there were 20%, who began to develop while 80% had not yet experienced development in speaking and for indicators of daring to express ideas there were 3 children ( 30%) began to develop while (70%) had not yet developed in cycle II, they had started to show a significant increase, this can be seen in the results of observation and the results of reflection show that they have developed (70%) and have not developed ( 30%). Meanwhile, the indicator for the courage to present ideas has increased (85%) and those that are starting to develop (15%).